Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Karyawan Studi Kasus Pada PT. Indo Metro Surya Andola - Sugeng, Sugeng; Fitriani, Fitriani; Aini, Farach Azizah (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of job satisfaction on turnover intention, to determine the effect of organizational commitment on turnover intention, and to determine that job satisfaction and organizational commitment simultaneously affect turnover intention. The research method used is a quantitative approach. The population in this study were employees of PT. Indo Metro Surya Andola. The instrument in this study used a questionnaire. Data analysis in this study used multiple linear regression to determine the dependent and independent variables with a computer program tool, namely SPSS version 25. The results show that 1) there is a negative influence between job satisfaction and turnover intention 2) there is a negative influence between organizational commitment and turnover intention 3) there is a negative influence between job satisfaction and organizational commitment on turnover intention.